The Effect of Competence, Work Discipline, and Motivation on Employee Performance in an Islamic Perspective (Study at Bank DKI Syariah Lampung Branch) - Noviyanti, Yeni Tri; Bahrudin, Moh.; Rosilawati, Weny; Amrina, Dania Hellin (Universitas Islam Negeri Raden Intan, 2024)
The achievement of a company is largely determined by the quality of the people who work in it. Changes in the environment require their ability to capture the phenomenon, analyze its impact and prepare steps to deal with these conditions. Superior performance has an impact on the company's reputation and growth. This research uses a quantitative approach with data collection methods in the form of questionnaires, observation and documentation. Primary data was obtained from answers to questionnaire questions given to all employees of Bank DKI Syariah Lampung Branch. While secondary data is obtained from various related references. The results showed that competence has a significant effect on employee performance, then the work discipline variable has a significant effect on employee performance, the motivation variable shows a significant effect on employee performance.